Juan Carlos : el rey de un pueblo / Paul Preston ; traducción de Eva Rodríguez Halffer y Gabriel Vázquez - Rodríguez Halfter, EvaVázquez, Gabriel; Preston, Paul
Bibliografía: p. 633-654. Índice alfabético